An evidence-based group coping intervention for women living with HIV and history of childhood sexual abuse. - Puffer, Eve S; Kochman, Arlene; Hansen, Nathan B; Sikkema, Kathleen J (International journal of group psychotherapy, 2011)
Women living with HIV/AIDS and a history of childhood sexual abuse often exhibit sexual trauma symptoms and elevated rates of HIV-risk behaviors. In this paper, we describe a coping skills group intervention that reduced traumatic stress and sexual-risk behavior in a recent randomized clinical trial. We focused on clinical issues that emerged among female participants receiving the intervention. Clinical observations showed that recognizing connections between trauma, psychological distress, and high risk behaviors was a new and powerful experience for many participants. Participants successfully applied psychoeducational material, expressing an increased sense of power and control over their relationships and behaviors as they developed more adaptive cognitive and behavioral skills. Women expressed high levels of satisfaction with the intervention. Recommendations for clinical practice are provided.
Keywords: Adaptation, Psychological; Adult; Child; Child Abuse, Sexual; Cognitive Therapy; Female; HIV Infections; Humans; Middle Aged; Psychotherapy, Group; Risk-Taking; Stress, Psychological; Treatment Outcome; Women